Influence of human capital supplies on the creation of information society and the innovation of industrial structures - Borowiec, Monika; Dorocki, Sławomir; Jenner, Bartosz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2009)
In the transformation process from the industrial phase of civilizational development to the information phase, the economic base of different scales of spatial structures undergoes fundamental changes. The result of this process is the transformation of the job market. The number of workers in traditional industrial sectors decreases as the result of the development of new sectors connected with computer industry, which leads to workers’ change in sectors of high technologies, both the industry and the services.This article presents the analysis of differentiation of European space and the changes of chosen indicators related to the quality of human capital which determine the development of information society and the growth of economic innovation.The authors of the article attempt to determine the relations between selected features, the dynamics of their development and the time correlation by means of a synthetic measure, related to the differentiation of intellectual potential and advanced economic technology in the analysed spatial structures (regions NUTS 2 and NUTS 1).The research takes into account the influence of particular empirical indicators on the value of the synthetic measure. This allows creation of a kind of hierarchy of European space according to the analysed features and the synthetic values determining the differentiation of the quality of intellectual supplies and economic innovation.